CRISPR/Cas9-mediated genome editing: from basic research to gene therapy - Goel, Rajeev (International Journal of Research in Medical Sciences, 2024)
CRISPR/Cas9 mediated genome editing is one of the most significant molecular tools discovered to edit the desired genes. It has ushered in a new era of novel possibilities of gene therapy. CRISPR/Cas9 system was originally observed as a part of the adaptive immune system in bacteria. It later on was adapted to carry precise and targeted alterations to the DNA in human cells to be used for gene therapy to correct genetic disorders and treat various severe diseases associated with the genetic changes. Besides this, the CRISPR/Cas9 system has been employed in pharmacogenomics to develop new drugs based on the patient’s genes, in modifying the organisms for research and even for diagnostic purposes in developing CRISPR based COVID-9 test. The recent approval of a CRISPR/Cas9 cellular gene therapy by FDA named “Casgevy” to treat sickle cell anemia is a testimonial to the potentials of CRISPR/Cas9 system in developing innovative gene therapies. This review details the mechanisms of CRISPR/Cas9 gene editing and its utilization in the ongoing clinical trials in the treatment of not only the monogenic disorders like sickle cell disease, thalassemia, and genetic blindness but also in treating multi-factorial diseases like cancers, cardiac diseases, diabetes, autoimmune diseases, viral infections such as human immunodeficiency virus (HIV) etc. An attempt has also been made to discuss the various limitations, challenges and ethical frameworks encompassing CRISPR/Cas9 based gene therapy in clinical settings.